Uncertainty evaluation for complex GPS characteristics. (December 2021) - Rosner, Paweł; Wojtyła, Mirosław; Gomez-Acedo, Eneko; Balsamo, Alessandro
Abstract: A proposal for estimating the uncertainty of coordinate measurements is presented, which can be applied in industrial conditions. The basis is the sensitivity analysis method supplemented with an experiment with the use of a non-calibrated object. The measuring task modelling procedure for complex geometrical characteristics is described. The results of research on the correlation of experimental results and the sensitivity analysis results are given.